The Influence of Job Characteristics and Work-Life Balance on Employee Performance with Mediation Digital Dexterity - Hanjaya, Yahya Kurnia; Mujanah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
This study investigates the influence of job characteristics and work-life balance on employee performance among vocational high school teachers, examining the mediating role of digital dexterity. The research employed a quantitative approach, surveying 51 teachers at SMK Ketintang Surabaya. Partial Least Square (PLS) analysis was used for hypothesis testing. The findings indicate that both job characteristics and work-life balance have a significant positive effect on digital dexterity. Furthermore, job characteristics, work-life balance, and digital dexterity all demonstrate a significant positive influence on employee performance. Digital dexterity acts as a significant mediator in these relationships. The model explained 62.9% of the variance in digital dexterity (moderate effect) and 75.9% of the variance in employee performance (substantial effect). Work-life balance exhibited a larger effect size on digital dexterity compared to job characteristics, while digital dexterity had the most substantial effect size on employee performance among the predictors. In conclusion, well-designed job roles and effective work-life balance are vital for enhancing teacher performance, both directly and by fostering digital dexterity. Educational institutions are advised to focus on improving job characteristics, supporting work-life balance, and investing in digital skills development for their teaching staff.